Hubungan Tingkat Stres dan Status Gizi dengan Gangguan Siklus Menstruasi pada Mahasiswi Tingkat Akhir Fakultas Kedokteran Universitas Swadaya Gunung Jati - Erika Nurfathya Zahra; Niklah Zaidah; Frista Martha Rahayu (Lembaga Pengembangan Kinerja Dosen, 2025)
During adolescence, girls experience their first menstruation, known as menarche. The repeated occurrence of menstruation each month establishes the menstrual cycle. Menarche is the first menstrual period experienced by adolescents, and a normal menstrual cycle occurs every 21–35 days. Several factors may contribute to menstrual cycle irregularities, including stress, physical activity, use of hormonal drugs, endocrine disorders, and nutritional status. To analyze the correlation between stress levels and nutritional status with menstrual cycles in final year students of the Faculty of Medicine at Swadaya Gunung Jati University. This study employed an analytical correlational method with a retrospective approach and a cross-sectional design. A purposive sampling technique was used, involving 93 female students. The study was conducted in May 2025. Stress levels were measured using the DASS-42 questionnaire, nutritional status was assessed using the Body Mass Index (BMI), and menstrual cycles were evaluated based on respondents’ menstrual history. Data analysis was performed using Spearman’s correlation test to examine the relationship between variables. The majority of respondents had normal stress levels (68.8%) and normal nutritional status (49.5%), as well as regular menstrual cycles (63.4%). The results of the Spearman test showed a significant relationship between stress levels and menstrual cycle disorders (p = 0.006; r = 0.285) as well as nutritional status with menstrual cycle disorders (p = 0.034; r = 0.22). Multivariate analysis indicated that stress levels is the most influential factor on menstrual cycle disorders (p = <0.001). There is a significant relationship between stress levels and nutritional status with menstrual cycle disorders, with stress levels exerting a greater influence than nutritional status.